A TiO2 embedded structure for perovskite solar cells with anomalous grain growth and effective electron extraction. Issue 4 (6th January 2017) - Wei, Dong; Ji, Jun; Song, Dandan; Li, Meicheng; Cui, Peng; Li, Yaoyao; Mbengue, Joseph Michel; Zhou, Wenjia; Ning, Zhijun; Park, Nam-Gyu
Abstract : The embedded structure of perovskite solar cells (PSCs) is a novel structure, which possesses excellent photovoltaic performance and better long-term stability than the mesoporous or planar structure. Abstract : The structure of the perovskite solar cells (PSCs) is either mesoporous or planar. Here, a novel structure for highly efficient and stable PSCs is proposed, i.e., an embedded structure, which combines the advantages of the mesoporous and planar structures. The embedded structure utilizes a TiO2 nanoparticle embedded perovskite (CH3 NH3 PbI3 ) film as the absorption layer. The presence of TiO2 nanoparticles in the perovskite film could improve the electron extraction, and promote the formation of a compact perovskite layer with large grains. Consequently, the performance of the PSCs is significantly improved with the efficiency increasing from 16.6% for the planar structure to 19.2% for the embedded structure, which is the best performance of the MAPbI3 -based PSCs. Furthermore, the TiO2 embedded perovskite films present better long-term stability than the pristine perovskite films, and the corresponding PSCs, which have no other chemical modifications, also show excellent stability with efficiency approaching 80% (for average) or 90% (for the best) after being exposed to air for 28 days without encapsulation.